Fruit and vegetable phytochemicals : chemistry, nutritional value and stability - Alvarez-Parrilla, Emilio; Gonzalez-Aguilar, Gustavo A.; Rosa, Laura A. de la (Wiley-Blackwell, 2010)
Presents scientists in the areas of food technology and nutrition with information about the chemical nature, classification and analysis of the main phytochemicals present in fruits and vegetables - polyphenols and carotenoids. This title analyzes the health benefits of these compounds, antioxidant and other biological activities.